China's Energy Transition Pathway in a Carbon Neutral Vision. (July 2022) - Zhang, Shu; Chen, Wenying
Abstract: China's energy system requires a thorough transformation to achieve carbon neutrality. Here, leveraging the highly acclaimed the Integrated MARKAL-EFOM System model of China (China TIMES) that takes energy, the environment, and the economy into consideration, four carbon-neutral scenarios are proposed and compared for different emission peak times and carbon emissions in 2050. The results show that China's carbon emissions will peak at 10.3–10.4 Gt between 2025 and 2030. In 2050, renewables will account for 60% of total energy consumption (calorific value calculation) and 90% of total electricity generation, and the electrification rate will be close to 60%. The energy transition will bring sustained air quality improvement, with an 85% reduction in local air pollutants in 2050 compared with 2020 levels, and an early emission peak will yield more near-term benefits. Early peak attainment requires the extensive deployment of renewables over the next decade and an accelerated phasing out of coal after 2025. However, it will bring benefits such as obtaining better air quality sooner, reducing cumulative CO2 emissions, and buying more time for other sectors to transition. The pressure for more ambitious emission reductions in 2050 can be transmitted to the near future, affecting renewable energy development, energy service demand, and welfare losses.